A Case-Control Study on Effect of Rotavirus Monovalent G9P[11] Vaccination on the Severity of Diarrhoea in Children Aged 2-24 Months in Indonesia - Fransiskus Koda; Andi Zulkifli; Ida Leida Maria; A Ummu Salmah; Anwar Mallongi (Medsci Publications, 2024)
Background: In Indonesia, rotavirus monovalent G9P[11] vaccine is the first rotavirus vaccine implemented through a government program and has never been evaluated. Makassar City is one of the 21 cities targeted for the introduction of rotavirus immunization in Indonesia. Aims/Objectives: To determine the association between rotavirus vaccination and the severity of diarrhoea in children aged 2-24 months. Methodology: Facility-based Case-Control Study design was conducted at Daya and Paramount hospital in Makassar City in January-February 2024. A total of 180 respondents participated (90 cases and 90 controls). The sampling method used was non-probability sampling, specifically the consecutive sampling technique. Data were analysed using the logistic regression test in Stata version 14. Results: Rotavirus vaccine status AOR = 4.25 (CI95% 1.82-9.90); P = 0.001. Not receiving the vaccine compared to receiving a partial dose of the vaccine COR = 4.03 (CI95% 1.79-9.16); P = 0.0002. Not receiving the vaccine compared to children receiving the full dose of the vaccine COR = 12.70 (CI95% 4.87-34.12); P = 0.0000. Duration of vaccine administration COR = 4.32 (CI95% 1.66-11.23); P = 0.0006. Conclusions: The rotavirus vaccine status was significantly associated with the severity diarrhoea in children aged 2-24 months.